Effect of peer motivation on smoking behaviour of male trainees in Malaysian allied health institutes - Mohammad Yusop, Marzani (2021)
Persistent motivation is essential for smokers to quit smoking. Therefore, peer motivation approach was adopted via a module in a smoking cessation program comprising 23 pages of guidance with regards to the transtheoretical model to be used in motivation sessions. This study involved 324 male smoker trainees at selected Ministry of Health Malaysia training institution. The peer motivation module was evaluated using a single-blind cluster randomisation parallel controlled trial design with three times evaluations; at baseline, three and six months after the intervention. The questionnaire used in this study was adopted from URICA DELTA 2004. Meanwhile, the Global Adult Tobacco Survey 2011 (GATS) was utilised to further examine the intervention in terms of knowledge, attitude, motivation, carbon monoxide and the number of cigarettes in subjects after three and six months. Results demonstrated that the intervention and control groups have significant differences in carbon monoxide (CO) levels at three and six months of evaluation data (p = 0.001). The mean CO levels in the intervention group showed a significant decrease at the three-month evaluation (9.14ppm, p<0.001) and six month evaluation (6.74ppm, p<0.001) when compared to the baseline (10.44 ppm). Overall data on knowledge showed that the mean value for the intervention group at baseline (10.87) had significantly increased to 12.38 (p<0.001) at three-month and 13.88 (p<0.001) at six-month evaluation. Similarly, the mean attitude score was observed to increase in the intervention group to 10.19(p<0.001) at three months and 10.59 (p<0.001) at six months. Data on motivation hadreduced from 1.43 at baseline to 1.15 (p>0.05) at three months and 1.08 (p>0.05) at six months. Meanwhile, data on the number of cigarettes showed a 9.93 mean value in the interventiongroup at baseline and decreased to 6.19 (p<0.001) at three months and 3.48 (p<0.001) at six months. The peer support approach effectively reduced the CO level among male smoker trainees in Allied Health Institutes, Malaysia, showing its great potential to be implemented in all training institutes. This study found that good knowledge, favourable attitudes and good motivation were key drivers of a smoker’s success in quitting smoking.